Melatonin for the promotion of sleep in adults in the intensive care unit - Lewis, Sharon R (Cochrane Database Syst Rev, 2018)
BACKGROUND: Patients in the intensive care unit (ICU) experience sleep deprivation caused by environmental disruption, such as high noise levels and 24‐hour lighting, as well as increased patient care activities and invasive monitoring as part of their care. Sleep deprivation affects physical and psychological health, and patients perceive the quality of their sleep to be poor whilst in the ICU. Artificial lighting during night‐time hours in the ICU may contribute to reduced production of melatonin in critically ill patients. Melatonin is known to have a direct effect on the circadian rhythm, and it appears to reset a natural rhythm, thus promoting sleep. OBJECTIVES: To assess whether the quantity and quality of sleep may be improved by administration of melatonin to adults in the intensive care unit. To assess whether melatonin given for sleep promotion improves both physical and psychological patient outcomes. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL; 2017, Issue 8), MEDLINE (1946 to September 2017), Embase (1974 to September 2017), the Cumulative Index to Nursing and Allied Health Literature (CINAHL) (1937 to September 2017), and PsycINFO (1806 to September 2017). We searched clinical trials registers for ongoing studies, and conducted backward and forward citation searching of relevant articles. SELECTION CRITERIA: We included randomized and quasi‐randomized controlled trials with adult participants (over the age of 16) admitted to the ICU with any diagnoses given melatonin versus a comparator to promote overnight sleep. We included participants who were mechanically ventilated and those who were not mechanically ventilated. We planned to include studies that compared the use of melatonin, given at an appropriate clinical dose with the intention of promoting night‐time sleep, against no agent; or against another agent administered specifically to promote sleep. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed studies for inclusion, extracted data, assessed risk of bias, and synthesized findings. We assessed the quality of evidence with GRADE. MAIN RESULTS: We included four studies with 151 randomized participants. Two studies included participants who were mechanically ventilated, one study included a mix of ventilated and non‐ventilated participants and in one study participants were being weaned from mechanical ventilation. Three studies reported admission diagnoses, which varied: these included sepsis, pneumonia and cardiac or cardiorespiratory arrest. All studies compared melatonin against no agent; three were placebo‐controlled trials; and one compared melatonin with usual care. All studies administered melatonin in the evening. All studies reported adequate methods for randomization and placebo‐controlled trials were blinded at the participant and personnel level. We noted high risk of attrition bias in one study and were unclear about potential bias introduced in two studies with differences between participants at baseline. It was not appropriate to combine data owing to differences in measurement tools, or methods used to report data. The effects of melatonin on subjectively rated quantity and quality of sleep are uncertain (very low certainty evidence). Three studies (139 participants) reported quantity and quality of sleep as measured through reports of participants or family members or by personnel assessments. Study authors in one study reported no difference in sleep efficiency index scores between groups for participant assessment (using Richards‐Campbell Sleep Questionnaire) and nurse assessment. Two studies reported no difference in duration of sleep observed by nurses. The effects of melatonin on objectively measured quantity and quality of sleep are uncertain (very low certainty evidence). Two studies (37 participants) reported quantity and quality of sleep as measured by polysomnography (PSG), actigraphy, bispectral index (BIS) or electroencephalogram (EEG). Study authors in one study reported no difference in sleep efficiency index scores between groups using BIS and actigraphy. These authors also reported longer sleep in participants given melatonin which was not statistically significant, and improved sleep (described as "better sleep") in participants given melatonin from analysis of area under the curve (AUC) of BIS data. One study used PSG but authors were unable to report data because of a large loss of participant data. One study (82 participants) reported no evidence of a difference in anxiety scores (very low certainty evidence). Two studies (94 participants) reported data for mortality: one study reported that overall one‐third of participants died; and one study reported no evidence of difference between groups in hospital mortality (very low certainty). One study (82 participants) reported no evidence of a difference in length of ICU stay (very low certainty evidence). Effects of melatonin on adverse events were reported in two studies (107 participants), and are uncertain (very low certainty evidence): one study reported headache in one participant given melatonin, and one study reported excessive sleepiness in one participant given melatonin and two events in the control group (skin reaction in one participant, and excessive sleepiness in another participant). The certainty of the evidence for each outcome was limited by sparse data with few participants. We noted study limitations in some studies due to high attrition and differences between groups in baseline data; and doses of melatonin varied between studies. Methods used to measure data were not consistent for outcomes, and use of some measurement tools may not be effective for use on the ICU patient. All studies included participants in the ICU but we noted differences in ICU protocols, and one included study used a non‐standard sedation protocol with participants which introduced indirectness to the evidence. AUTHORS' CONCLUSIONS: We found insufficient evidence to determine whether administration of melatonin would improve the quality and quantity of sleep in ICU patients. We identified sparse data, and noted differences in study methodology, in ICU sedation protocols, and in methods used to measure and report sleep. We identified five ongoing studies from database and clinical trial register searches. Inclusion of data from these studies in future review updates would provide more certainty for the review outcomes.